European Association of Urology and European Society for Paediatric Urology guidelines on paediatric urinary stone disease: review - pediatric urology - Tekgul, Serdar; Stein, Raimund; Bogaert, Guy; Nijman, Rien J. M.; Quaedackers, Josine; 't Hoen, Lisette; Silay, M. Selcuk; Radmayr, Christian; Doğan, Hasan Serkan (European urology focus, 2022)
Context - Paediatric stone disease is an important clinically entity and management is often challenging. Although it is known that the condition is endemic in some geographic regions of the world, the global incidence is also increasing. Patient age and sex; the number, size, location, and composition of the stone; and the anatomy of the urinary tract are factors that need to be taken into consideration when choosing a treatment modality. - Objective - To provide a general insight into the evaluation and management of urolithiasis in the paediatric population in the era of minimally invasive surgery. - Evidence acquisition - A nonsystematic review of the literature on management of paediatric urolithiasis was conducted with the aim of presenting the most suitable treatment modality for different scenarios. - Evidence synthesis - Because of high recurrence rates, open surgical intervention is not the first option for paediatric stone disease, except for very young patients with very large stones in association with congenital abnormalities. Minimally invasive surgeries have become the first option with the availability of appropriately sized instruments and accumulating experience. Extracorporeal shockwave lithotripsy (SWL) is noninvasive and can be carried out as an outpatient procedure under sedation, and is the initial choice for management of smaller stones. However, for larger stones, SWL has lower stone-free rates and higher retreatment rates, so minimally invasive endourology procedures such as percutaneous nephrolithotomy and retrograde intrarenal surgery are preferred treatment options. - Conclusions - Contemporary surgical treatment for paediatric urolithiasis typically uses minimally invasive modalities. Open surgery is very rarely indicated. - Patient summary - Cases of urinary stones in children are increasing. Minimally invasive surgery can achieve high stone-free rates with low complication rates. After stone removal, metabolic evaluation is strongly recommended so that medical treatment for any underlying metabolic abnormality can be given. Regular follow-up with imaging such as ultrasound is required because of the high recurrence rates.